2011
DOI: 10.1007/s10548-011-0214-x
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenic Networks in Two Patients with Hypothalamic Hamartoma

Abstract: Hypothalamic hamartomas (HH) are typically associated with gelastic seizures but also implicated in the genesis of other seizure types. In order to identify networks involved in seizure generation, we performed EEG-fMRI in two adult patients with HH, the first with predominantly gelastic seizures and the second with complex partial and no typical gelastic seizures. The ictal and interictal analysis of the patient with gelastic seizures revealed the involvement of the HH, the cingulate gyrus, the precuneus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Additionally, stimulation of a small fiber bundle within the dorsal midbrain tegmentum reportedly induced a laughing-like reaction in primates (Weinstein and bender, 1943). The findings of previous EEG-fMRI studies with a smaller number of patients having HH (Kokkinos et al, 2012;Leal et al, 2009) are consistent with the existence of a network including the mammillo-thalamo-cingulate tract (Kahane et al, 2003). Some patients in our study showed involvement of the hippocampi and thalamus (see Fig.…”
Section: Strength Of This Studymentioning
confidence: 67%
“…Additionally, stimulation of a small fiber bundle within the dorsal midbrain tegmentum reportedly induced a laughing-like reaction in primates (Weinstein and bender, 1943). The findings of previous EEG-fMRI studies with a smaller number of patients having HH (Kokkinos et al, 2012;Leal et al, 2009) are consistent with the existence of a network including the mammillo-thalamo-cingulate tract (Kahane et al, 2003). Some patients in our study showed involvement of the hippocampi and thalamus (see Fig.…”
Section: Strength Of This Studymentioning
confidence: 67%
“…Kokkinos et al 65 performed EEG-fMRI studies in 2 patients with HHs and differing seizure presentations (one patient had predominantly gelastic seizures and the other had complex partial seizures without typical gelastic features) to determine any differences in the epileptogenic pathways. On interictal and ictal EEG-fMRI, they found that in the patient with gelastic seizures many areas outside the HH were involved in seizure onset, including the thalamus, cingulate gyrus, precuneus, and the frontal lobe.…”
Section: Functional Mrimentioning
confidence: 99%
“…Although the study did reveal commonalities in the epileptogenic pathways for both types of seizures in this limited study, the authors concluded that a case could be made for either an independent epileptogenic focus secondary to the HH or secondary seizure generation from the HH itself. 65 …”
Section: Functional Mrimentioning
confidence: 99%
“…The other 20 % of the operations were extra-temporal epilepsy cases with focal cortical resections and occasionally multilobar resections. Acute intraoperative ECoG is utilized in most temporal and extra-temporal cases for confirmation of epileptogenicity and modifications of resections in selected cases [26, 59, 60]. Follow-up information is available on a yearly basis for at least 90 % of the operated patients with 80 % of the patients having an Engel class I outcome, 15 % a class II–III, and 5 % a class IV outcome.…”
Section: Resultsmentioning
confidence: 99%